2021
DOI: 10.3390/ijerph18062814
|View full text |Cite
|
Sign up to set email alerts
|

Highlights of Current Dietary Guidelines in Five Continents

Abstract: The dietary guidelines as well as the organizations that establish the recommendations are not homogeneous across regions of the world. Each country utilizes specific icons to better describe to the public easy ways to follow specific recommendations, including the use of pyramids, plates, and other forms of presenting key information. All dietary guidelines are updated within certain periods to ensure that new findings or specific changes are communicated to the public. The purpose of this commentary is to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 17 publications
0
33
0
2
Order By: Relevance
“…In particular, the importance of addressing healthy dietary behavioral patterns represents a constant concern. State-of-the-art outlines have reported an update for healthy eating across five continents and for Mediterranean diet, with physical activity being an inherent component [ 22 , 23 ]. Such initiatives, however, seem to be potentially challenging due to adolescents’ poor well-being.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the importance of addressing healthy dietary behavioral patterns represents a constant concern. State-of-the-art outlines have reported an update for healthy eating across five continents and for Mediterranean diet, with physical activity being an inherent component [ 22 , 23 ]. Such initiatives, however, seem to be potentially challenging due to adolescents’ poor well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies suggest that adherence to the MD is associated with lower abdominal adiposity and reduced weight gain [ 24 , 25 ], with a beneficial effect on anthripometric parameters and cardiometabolic risk factors. Moreover, MD has social and environmental benefits, centered on sustainability [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that an optimal nutritional status can enhance the effects of training, speeding up recovery and optimizing body composition [33]. The dietary culture of the Spanish population is within the framework of the Mediterranean diet [34][35][36]. This one is characterized by being a balanced diet that provides sufficient calories in the right proportions through high consumption of vegetables, legumes, fruits, nuts, cereals, and olive oil, moderate consumption of fish, eggs, and dairy products, preferably yogurt or cheese, and a lower intake of meat and less consumption of animal fats [37].…”
Section: Introductionmentioning
confidence: 99%